SIMPLE CYCLIC MOVEMENTS AS A DISTINCT AUTISM FEATURE - COMPUTATIONAL APPROACH - Dobosz, Krzysztof; Mikołajewski, Dariusz; Wójcik, Grzegorz Marcin; Duch, Włodzisław (Computer Science, 2013)
Diversity of symptoms in autism dictates a broad definition of Autism Spectrum of Disorders(ASD). Each year percentage of children diagnosed with ASD is growing. One common diag-nostic feature in individuals with ASD is the tendency to atypical simple cyclic movements.The motor brain activity seems to generate periodic attractor state that is hard to escape.Despite numerous studies scientists and clinicians do not know exactly if ASD is a result ofa simple but general mechanism, or a complex set of mechanisms, both on neural, molecularand system levels. Simulations using biologically relevant neural network model presentedhere may help to reveal simplest mechanisms that may be responsible for specific behavior.Abnormal neural fatigue mechanisms may be responsible for motor as well as many if notall other symptoms observed in ASD.